Comparison Of Alanine Aminotransferase (Alt) Examination Using Serum And Edta Plasma Samples - Nurdianty Anwar, Eka; Eka Tresnaningrum, Meilinia; Parwito, Parwito; Arifin, Ismail (Jurnal Sains Kesehatan, 2023)
Alanine aminotransferase ( ALT ) is an enzyme made in liver cells. ALT is mainly found in the liver and is also found in small amounts in the heart and skeletal muscles. Serum and plasma EDTA can be used in the alanine aminotransferase (ALT) assay. The purpose of this study was to compare ALT examination using EDTA serum and plasma samples. This research was carried out in the Clinical Chemistry laboratory of the Harapan Bangsa Health Analyst Academy. This study using primary data capture technique sample Quota Sampling. The samples used were venous blood samples from 33 students of the Harapan Bangsa Health Analyst Academy. The type of research used in this research is observational. The data obtained were processed and tested with the t statistic test ( Paired Sample t-Test ) so that it can be concluded: " there is no significant difference " between ALT examination using serum and plasma EDTA samples, where t count 1.978 t table 2.036.